Controversials of Microscopic Colitis - Mihaly, Emese; Patai, Árpád; Tulassay, Zsolt (Frontiers in Medicine, 2021)
Microscopic colitis (MC) has become a disease with increased awareness since new data of the pathogenesis, diagnosis and therapy are arising. The incidence of MC is increasing, reaching in some populations levels similar to inflammatory bowel disease (IBD). But some aspects of MC are still controversial. It is not known whether the microbiom changes play a role in the pathogenesis and what is in the background of the subtypes transforming to each other. Is there a connection between MC and IBD or why the histological changes do not follow the clinical activity. We do not know what is the etiology of the incomplete MC and what is the natural course of it. The association of MC with celiac disease is well known- is there a common pathogenesis? Non-steroidal anti-inflammatory drugs (NSAIDs) are well known for their colonopathy side-effects. What is the reason to develop NSAID colonopathy in some cases or MC in the others? Is there an altered metabolism or genetic origin in the background? The MC treatment is budesonide, but the relapse rate is high, as well. Why would biologics be effective in these cases when budesonide is not?